Pembinaan analisis data dan informasi statistik perencanaan pembangunan daerah [Development of statistical data analysis and information for regional development planning] - Marzuki, Marzuki; Ula, Akramul; Munawar, Munawar; Rasudin, Rasudin; Zulfan, Zulfan; Zuhra, Rahma; Usman, Tarmizi; Iqbal, Muhammad (Universitas Syiah Kuala, 2024)
The purpose of this development activity is to enhance skills in planning, data analysis, and the use of information technology so that the Subulussalam City Government can improve the quality of planning documents produced, respond to the needs of the community, and provide a good understanding to employees related to statistical analysis. The method of implementing this activity is through training or seminars held on October 5, 2023, at the Regional Development Planning Agency (Bappeda) Hall of Subulussalam City for approximately 3 hours. The material presented includes basic concepts of statistical analysis, data analysis techniques, and the application of statistical analysis in regional development planning. Three main challenges in statistical analysis of regional development data include data limitations, data collection errors, and data processing errors. These challenges can be overcome by increasing understanding of methodology, quantity and quality of human resources, and inter-agency coordination. Statistical analysis in regional development planning can result in more targeted regional development planning and can identify challenges and opportunities to achieve sustainable development plans. Statistical analysis in regional development planning is important to be used as the basis for objective policies.